Performance evaluation of oscillatory baffle Bunsen reactor in iodine sulfur thermochemical process for hydrogen production - V Nafees Ahmed; A Shriniwas Rao (Clean Technologies and Recycling, 2023)
Hydrogen is an environmentally attractive transportation fuel that can replace fossil fuels. The iodine-sulfur (I-S) thermo-chemical process involves three reaction steps. The Bunsen reaction is one of the main reaction steps of I-S process and plays an important role in defining overall process efficiency. Different types of reactors are being studied, including the oscillatory baffle Bunsen reactor. The reactor selection is based on process intensification and process integration, i.e., reaction and separation in the single equipment. Simulations are performed for two-dimensional cases by solving incompressible Navier-Stokes equations along with continuity equation, the geometry chosen is of single section in the column and diameter of 50 mm and baffle spacing of 50, 75,100 mm i.e. 1, 1.5 and 2 times the diameter of column and baffle free area 22%. The residence time distribution experiments are carried out in a metallic reactor with NaCl as a tracer operated at different frequencies, amplitudes and flow rates. D/uL is evaluated from experimental curves. The power per unit mass is compared for oscillatory baffled column and stirred tank for a semi-batch process. From the numerical simulations, good eddy interactions are present at higher frequencies and amplitudes and at a baffle spacing of 1.5 times the diameter of the column. Residence time distribution analysis gives a lower dispersion number at medium frequencies and higher amplitudes with constant flow rate. If the flow rates are high, then it is better to operate at higher frequencies and amplitudes to achieve plug flow behavior. Power per unit mass is less for oscillatory baffle column compared to the stirred tank of given configuration. With better mixing performance and less power per unit volume, the oscillatory baffle column is a good alternative to other columns.